2010
DOI: 10.1002/j.2158-1592.2010.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Logistics Strategy: 1990–2008

Abstract: For over 45 years, the roles of logistics in the firm have been a topic of interest to practitioners, teachers, and researchers. In the 1970's, logistics' role in organizational strategy emerged as a topic of discussion. During the 1980's, Bowersox and Daugherty (1987) presented a typology which postulated three dimensions of logistics strategy: process; market; and information. Their typology has inspired a stream of empirical research over the last two decades which examined it from different perspectives. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 8 publications
1
34
1
4
Order By: Relevance
“…Strategiczne zarządzanie logistycznymi potencjałami sukcesu przedsiębiorstwa może opierać się na trzech podstawowych orientacjach [Autry, Zacharia, Lamb 2008;Bowersox, Daugherty 1987;Clinton i in. 1996;McGinnis, Kohn, Spillan 2010;Mollenkopf, Dapiran 2005]:…”
Section: Strategiczne Aspekty Zarządzania Logistycznymi Potencjałami unclassified
“…Strategiczne zarządzanie logistycznymi potencjałami sukcesu przedsiębiorstwa może opierać się na trzech podstawowych orientacjach [Autry, Zacharia, Lamb 2008;Bowersox, Daugherty 1987;Clinton i in. 1996;McGinnis, Kohn, Spillan 2010;Mollenkopf, Dapiran 2005]:…”
Section: Strategiczne Aspekty Zarządzania Logistycznymi Potencjałami unclassified
“…Finally, McGinnis et al (2010) compared logistics strategy evolution from 1990 to 2008 using the Bowersox and Daugherty dimensions (Process Strategy, Market Strategy, and Information Strategy) as independent variables and three dependent variables (Logistics Coordination Effectiveness, Customer Service Effectiveness, and Company/Division Competitive Responsiveness) to identify and evaluate the changes, if any, that occurred in logistics strategy over that period. The authors concluded that:…”
Section: Assessment Of Logistics Strategymentioning
confidence: 99%
“…Collection of the 1990 data is described in McGinnis and Kohn (1993), collection of the 1994 data is described in Kohn and McGinnis (1997a, b), collection of the 1999 data is described in McGinnis and Kohn (2002), and 2008 data collection is described in McGinnis et al (2010). After examining the means, standard deviations, and reliability coefficients of the variables during the four time periods the authors concluded that the data were satisfactory for inclusion in the following analysis.…”
Section: Data Collectionmentioning
confidence: 99%
“…To date, most research on logistics strategy has turned its focus towards individual functional operations in isolation (e.g. Autry et al, 2008;McGinnis et al, 2010), and has failed to link logistics with overall company goals such as profitability and growth. To advance logistics research, it may benefit from borrowing theory from other disciplines (Stock, 1997).…”
Section: In This Article the Strategic Role Of Logistics Is Focused mentioning
confidence: 99%